Claudin-3 and occludin content in the glands of colonic mucosa devoid from fecal stream submitted to topical intervention with oil extract of Curcuma longa - Martinez,Carlos Augusto Real (2017)
Abstract Purpose: To evaluate the inflammatory intensity and measure the tissue content of the proteins claudin-3 and occludin in the colonic mucosa without fecal stream submit to intervention with curcumin. Methods: Thirty-six rats were submitted to a proximal colostomy and a distal mucous fistula and divided into two groups according to sacrifice to be performed two or four weeks. Each group was divided into three subgroups according daily application of enemas containing saline, curcumin at 50 mg/kg/day or 200 mg/kg/day. Colitis was diagnosed by histological analysis. Claudin-3 and occludin were determined by immunohistochemistry. The tissue content of claudin-3 and occludin were quantified by computer-assisted image analysis. Mann-Whitney, Student t and ANOVA tests were used to analyze the results establishing the level of significance of 5% for both (p<0.05). Results: Curcumin at both concentrations reduces the inflammation and preserves the tissue content of the proteins claudin-3 and occludin, which was related to the concentration used and to the time of the intervention. Conclusion: The application of enemas with curcumin reduces inflammation and preserves the tissue content of the proteins claudin-3 and occludin in the colonic mucosa devoid from the fecal stream.